Analysis of Iranian passengers' behavior in choosing type of carrier in international air travel to East Asia. (September 2016) - Saffarzadeh, Mahmoud; Mazaheri, Akram; Tari, Majid Zabihi; Seyedabrishami, Seyedehsan
Abstract: Increased demand for East Asia flights from Tehran has intensified competition between Iranian and foreign carriers. In addition, the entrance of low-cost carriers (LCC) will make this competitive market even more intense. In this condition, carriers are striving to gain more market share by improving services and discounting their fares. Therefore, analyzing air travel demand is valuable for carriers' long term and short term planning. This study empirically investigates passengers' behavior in choosing five types of carriers in many groups of passengers using multinomial logit (MNL) and nested logit (NL) models. The data were collected through the stated preference (SP) questionnaire designed based on orthogonal main-effect. The main survey was conducted in the Imam Khomeini International (IKI) airport in July 2013 where 480 questionnaires were collected through face-to-face interviews. The results show that the ticket fare, the possibility of travel on desired date and time, international air travel experience, Frequent-flyer program (FFP) membership status, marital status, and gender are statistically significant contributors in explaining carrier choice. Interaction effects between trip purpose and ticket fare are statistically significant in choosing carriers. The results further indicate that business travelers are more willing to pay than non-business travelers for flights on desired date and time, although varying by type of carrier. Highlights: This study investigates passengers' behavior in choosing five types of carriers. The Iranian international passengers' travel experience and FFP membership have significant effects on carrier choice. The carrier ticket fare and flexibility in date and time are the most influential attributes on Iranian passengers' choice. The results indicate that business travelers are willing to pay for flights on desired date and time.